BIOSYNTHESIS AND CHARACTERIZATION OF NiO THIN FILM USING LEAF EXTRACTION OF LEEK PLANT BY USING THE SPRAY PYROLYSIS TECHNIQUE - Abdullah, Lilav; Abdulrahman, Ahmed (Science Journal of University of Zakho, 2026)
Nickel oxide (NiO) nanoparticles were successfully synthesized by a green and affordable method, and an aqueous extract of Fresh Leek leaf was employed as a bio-reducing and capping agent. The synthesis was accomplished in two-steps: the seed layer on glass substrate was deposited by a slightly modified spray pyrolysis method employing nickel acetate precursor and undergoing spin coating technique; one followed by the growth of nanoparticles from a solution of nickel nitrate at different pH (9, 10 and 11). The elemental, structural, morphological and optical properties of the biosynthesized NiO NPs were fully determined. Field emission scanning electron microscopy (FESEM) showed that the spherical nanoparticles were well dispensed and their mean size depended on the pH of the growth solution. The development of cubic crystal structure was confirmed by its XRD analysis. FTIR spectroscopy was used to determine the reducing and stabilizing groups (functionalization) that acted in the reduction/stabilization process. UV-Vis. spectra: λ max at 360–370 nm, and the increasing in band gap value from 3.61 to 3.76 eV that indicates quantum confinement effect has been verified. Energy dispersive X-ray (EDX) analysis verified that nanoparticles have high purity and stoichiometry. The results revealed that the plant-assisted preparation accompanied by spray pyrolysis is a promising environmentally friendly approach for fabrication of high quality NiO NPs with potential applications in different technological arenas.